2014
DOI: 10.1515/hc-2013-0239
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of plants from the genus Neolitsea

Abstract: The genus Neolitsea (Lauraceae) contains over 85 species distributed around the world. These plants have been found to be rich in sesquiterpenes, triterpenes, steroids, and alkaloids. This review summarizes the phytochemical progress and list of all the constituents isolated from the genus Neolitsea over the past few decades. Some biological activities of compounds isolated from this genus are also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For this kind of compounds, there were a few reports on pharmacological activities, and there are no clear structure-activity relationships for the time being. But according to Qiu's experiment, we can observe that cyclopregnane alkaloids display strong cytotoxic activity against HeG2 and K562 cell lines through compounds 42, 43, 44, 45, and 46 (IC 50 <6 mM) and showed no cytotoxicity against A549, SW480, SMMC-7721, HL-60, and MCF-7 cell lines through compounds 47, 48, 49, and 50 (IC 50 >40 mM) (Figure S4) (23).…”
Section: Cyclopregnane Alkaloidsmentioning
confidence: 94%
“…For this kind of compounds, there were a few reports on pharmacological activities, and there are no clear structure-activity relationships for the time being. But according to Qiu's experiment, we can observe that cyclopregnane alkaloids display strong cytotoxic activity against HeG2 and K562 cell lines through compounds 42, 43, 44, 45, and 46 (IC 50 <6 mM) and showed no cytotoxicity against A549, SW480, SMMC-7721, HL-60, and MCF-7 cell lines through compounds 47, 48, 49, and 50 (IC 50 >40 mM) (Figure S4) (23).…”
Section: Cyclopregnane Alkaloidsmentioning
confidence: 94%
“…Ethanolic extracts of leaves of N. sericea var. aurata showed the presence of 14 new alkaloids using the HPLC-SPE-NMR technique 2 and 37 known alkaloids were reported from this genus 3 . The genus is rich in alkaloids, mainly isoquinoline, and aporphine 4 , sesquiterpenes, triterpenes, and steroids 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, IOP Publishing doi:10.1088/1755-1315/1356/1/012010 2 the application is in the form of water infusion, or decoction. Several studies reported that L. speciosa, C. parthenoxylon, and O. indicum have the potential to be antiulcer, antidiabetic, anti-inflammatory, and antilipidemic potentials but they don't lower liver enzyme levels [7][8][9]. The purpose of the study was to evaluate the flavonoids, tannins, steroids, and alkaloids present in the aqueous extracts of C. parthenoxylon, O. indicum, and L. specioca, as well as their efficacy in reducing cholesterol and hemoglobin glycosylation.…”
Section: Introductionmentioning
confidence: 99%